Elaboração de um modelo de plano de gestão de manutenção para um edifício residencial na cidade de Campo Mourão-PR - Silva, Giovanna Bestetti Martins da (2025)
Although preventive maintenance is very common in several sectors of the industry, this practice has still not been widely adopted in the construction industry. As a result, there has been a dilemma regarding responsibilities for building failures over time. Given this context, the main objective of this study is to propose a maintenance management plan for a multi-story, multi-family building in the city of Campo Mourão, with the aim of assisting users in the practice of maintenance and clarifying the warranty periods and durability of the building systems, in accordance with the essential regulations for the preparation of the maintenance management plan. To this end, a study of the standards related to the subject, academic papers and models of maintenance management plans were carried out, as well as an analysis of the projects of the building selected as a reference for the preparation of the plan. With the information collected, tables were prepared that reference, according to the standards, the warranty periods of the systems and subsystems of the building in question, as well as the expected performance period of these. Furthermore, the importance of the verification record to prove that periodic maintenance is carried out by the building user was portrayed.